PERKEMBANGAN PROGRAM TV PADA ERA REVOLUSI INDUSTRI - Herdi Herdi (Institut Seni Budaya Indonesia Bandung, 2020)
This paper analyzes the form of TV programs in the 4.0 era. This research is a qualitative research that aims to describe the development of television programs from time to time. Research data is generated from library research and virtual observations by paying attention to TV programs recorded on Youtube. The Industrial Revolution made changes to Television Programming from the 1970s to the 1980s. In the past, there was a change in technology from black and white television to color television. There were not many choices of television programs, because at that time there were only those TV programs that people could watch and enjoy. However, now in the era of the industrial revolution 4.0. Television program creators are generally stuck with the convenience of an integrated machine with an internet network (internet of things) without heeding Intellectual Property Rights. This is also what is allegedly causing a decline in the creativity of television program creators in the industrial era 4.0. If a solution is not immediately found, the popularity of TV programs is predicted to be killed by the popularity of creative content on social media networks.